BILINGUAL POET – ANBAR OTIN - Pardaeva, Nigora (АКТУАЛЬНОЕ В ФИЛОЛОГИИ, 2021)
The article reviews the work of poet Anbar Otin, who wrote in Uzbek and Tajik. There is a brief information about the poetics, content and ideas of the Uzbek and Tajik poems of the poet. Some of his poems in Tajik have been analyzed